2017
DOI: 10.2807/1560-7917.es.2017.22.18.30527
|View full text |Cite
|
Sign up to set email alerts
|

Passive enhanced safety surveillance for Vaxigrip and Intanza 15 µg in the United Kingdom and Finland during the northern hemisphere influenza season 2015/16

Abstract: Enhanced safety surveillance (ESS) was conducted in the United Kingdom and Finland for Vaxigrip and Intanza 15 µg to comply with the European Medicines Agency interim guidance aimed to detect any potential increase in reactogenicity in near real time following the annual update of the influenza vaccine strain composition. This pilot passive ESS was established to strengthen safety monitoring by facilitating spontaneous vaccinee reports and estimating near real-time vaccinee exposure. The primary objective was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 10 publications
(6 reference statements)
0
24
0
Order By: Relevance
“…Early influenza vaccine safety surveillance aims to identify potential new safety concerns as soon as possible, before the peak period of mass immunization. 2 As in previous EPSS studies, 8,9 no safety issues were observed during the NH 2017/ 18 influenza season in participants receiving IIV3-ID or IIV3. Similarly, for IIV4, the EPSS showed no difference between the reported rates of ARs and those expected based on clinical trial data.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Early influenza vaccine safety surveillance aims to identify potential new safety concerns as soon as possible, before the peak period of mass immunization. 2 As in previous EPSS studies, 8,9 no safety issues were observed during the NH 2017/ 18 influenza season in participants receiving IIV3-ID or IIV3. Similarly, for IIV4, the EPSS showed no difference between the reported rates of ARs and those expected based on clinical trial data.…”
Section: Discussionmentioning
confidence: 70%
“…ARs reported by each participant were collected using an Information Request Management System and were confirmed by a structured telephone interview as described previously. 8,9 All events reported spontaneously by participants or healthcare professionals were considered as suspected ARs (i.e., vaccinerelated) unless the participants specifically stated that they believed the events were unrelated or that a causal relationship could be excluded. No causality assessment was requested from the participants or healthcare professionals.…”
Section: Study Conduct and Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides clinical trials, many commercial MN products have been developed for vaccination and are available nowadays. These commercial products, for example, Nanopatch TM [159], Fluzone Intradermal ® [160], and Intanza ® [161], have been published in journals, and contributed to public health against pestilence [162,163].…”
Section: Vaccine Deliverymentioning
confidence: 99%